0
$\begingroup$

I follows these steps:

  1. Define $e^z:=\sum_{k=0}^{\infty}\frac{z^k}{k!}$.
  2. Show thatthe series is absolutely convergent.
  3. Define $\sin(z):=\frac{e^{iz}-e^{-iz}}{2i}$, and $\cos(z):=\frac{e^{iz}+e^{-iz}}{2}.$
  4. Derive $$ \sin(z)=\sum_{n=0}^\infty\frac{(-1)^n}{(2n+1)!}z^{2n+1}, \quad \cos(z)=\sum_{n=0}^\infty\frac{(-1)^n}{(2n)!}z^{2n}. $$ just by sum manipulation.

Can I now trust that $\frac{e^{iz}+e^{-iz}}{2}=\sum_{n=0}^\infty\frac{(-1)^n}{(2n+1)!}z^{2n+1}$? Or: is this question equivalent to the following lemma?

Lemma If $f(x)=\sum a_k$ and $g(x)=\sum b_k$ are abs. conv. then (a) $\sum ca_k$ is abs. conv. and $cf=\sum ca_k$; (b) $\sum (a_k+b_k)$ is abs. conv. and $f+g=\sum (a_k+b_k)$.

Is the given lemma treated in a standard textbook or is assumed as evident?

$\endgroup$
3
$\begingroup$

Right now, I can't provide an example of a textbook proving that lemma. But it's quite simple:

(a) If $\sum_{n=0}^\infty\lvert a_k\rvert$ converges, then $\sum_{n=0}^\infty\lvert ca_k\rvert$ converges too, since it is equal to $\sum_{n=0}^\infty\lvert c\rvert\lvert a_k\rvert$.

(b) If both series $\sum_{n=0}^\infty\lvert a_k\rvert$ and $\sum_{n=0}^\infty\lvert b_k\rvert$ converge, then $\sum_{n=0}^\infty\lvert a_k+b_k\rvert$ converges too, since$$(\forall k\in\mathbb Z^+):\lvert a_k+b_k\rvert\leqslant\lvert a_k\rvert+\lvert b_k\rvert$$and $\sum_{n=0}^\infty\bigl(\lvert a_k\rvert+\lvert b_k\rvert\bigr)$ converges.

$\endgroup$
  • $\begingroup$ If I understand your answer, you mean that the Lemma is needed, and I'm not making my life unnecessarily difficult (that was the spirit of my question). $\endgroup$ – Aaron Lenz May 14 at 8:12
  • $\begingroup$ Yes, the lemma is needed. No doubt about that. $\endgroup$ – José Carlos Santos May 14 at 8:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.